Anxiety Level and Risk Factors in Medical Students - Arisyna Arisyna; Florentina Sustini; Nalini Muhdi (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Medical students are more susceptible to anxiety than non-medical students. This study aimed to describe the anxiety level and its risk factors among the first, third, and fifth year medical students in Universitas Airlangga.Methods: We conducted cross-sectional study involving 195 medical students by consecutive sampling. The inclusion criteria in this study were all first, third, and fifth year medical students who were willing to participate in the study. The data was recorded using questionnaire of anxiety risk factors, Hamilton Rating Scale for Anxiety, and Miller and Smith Stress Vulnerability Scale. All data then was processed and analyzed descriptively.Results: From 195 students, 57 male (29.2%) and 138 female (70.8%) students participated, consisted of 63 first year, 68 third year, and 64 fifth year students. Anxiety mostly occurred in fifth year students (20.3%), followed by first year students (19%), and third year students (11.8%). Anxiety mostly occured in male (24.6%), at the age of 17 (33.3%), susceptible to stress (75%), dissatisfied with physical condition (29.2%), had chronic diseases (26.4%), on middle birth order (34.6%), had frequent conflict with parents in almost every month (50%), lived in dorm (20%), had no close friends (33.3%), perceived that health was not important (100%), orphaned (18.8%), low parental income (35%), overburdened with examination (26.3%), and dissatisfied with the examination criteria (26.5%).Conclusion: Fifth year medical students had the highest frequency of anxiety, while third year students had the lowest frequency. Nevertheless, based on the age, anxiety mostly occurred at the age of 17. These conditions were caused by some risk factors.